Kendala dan Persepsi Tenaga Kerja dalam Pengembangan Pariwisata di Pantai Pandawa Desa Kutuh, Kabupaten Badung - Sijabat, Dwinda Noveli Yanti; Sastrawan, I Gede Anom (JURNAL DESTINASI PARIWISATA, 2021)
Pandawa Beach is a tourism activity that develops with the participation of local communities. The workers who manage the activities on Pandawa Beach are the local people of Kutuh Village. This study aims to determine the constraints and perceptions of the Pandawa Beach workforce as the Local Community of Kutuh Village. This study was carried out by interviewing and distributing questionnaires. Based on interviews and questionnaires, it can be concluded that the overall perception of the workforce on their participation is positive. The obstacles experienced by Pandawa Beach workers are related to expertise and capital in developing tourism activities. However, all these obstacles have been resolved through monthly training and assistance in the form of a loan from the Village Credit Institution (LPD). Keyword: Tourism, Constraint, Perception, Participation